2005
DOI: 10.13181/mji.v14i3.192
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic dysfunction in type 2 diabetes mellitus patient without cardiovascular disease: the association with microalbuminuria

Abstract: Desember 2001, dilakukan pemeriksaan ekokardiografi untuk melihat fungsi diastolik ventrikel kiri dan dilakukan pemeriksaan urin mikroalbuminuria. Disfungsi diastolik ditemukan pada 73,7 % pasien DM tipe 2 tanpa mikroalbuminuria dan 66,7% pada DM tipe 2 dengan mikroalbuminuria. Tidak terdapat hubungan bermakna kejadian disfungsi diastolik pada kelompok DM tipe 2 dengan mikroalbuminuria maupun DM tipe 2 tanpa mikroalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Akiyama et al 23 reported that the odds of having LVDD in Japanese T2DM patients with albuminuria was about eight times more than those without albuminuria (OR 7.95, 95% CI: 1.74-21.6, p = 0.005). By contrast, Alwis et al 4 noted in their study on 28 T2DM patients without any cardiovascular disease that 73.7% of those without microalbuminuria and 66.7% of those with microalbuminuria had LVDD. Likewise, Yildirimturk et al 24 found among 50 diabetics, no significant differences in LV systolic and diastolic function between patients with or without MCA.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Akiyama et al 23 reported that the odds of having LVDD in Japanese T2DM patients with albuminuria was about eight times more than those without albuminuria (OR 7.95, 95% CI: 1.74-21.6, p = 0.005). By contrast, Alwis et al 4 noted in their study on 28 T2DM patients without any cardiovascular disease that 73.7% of those without microalbuminuria and 66.7% of those with microalbuminuria had LVDD. Likewise, Yildirimturk et al 24 found among 50 diabetics, no significant differences in LV systolic and diastolic function between patients with or without MCA.…”
Section: Discussionmentioning
confidence: 79%
“…Diabetes mellitus (DM) is associated with diverse cardiovascular conditions such as myocardial infarction, heart failure (HF), stroke and diabetic cardiomyopathy (DMCMP), which are the leading causes of diabetes-related morbidity and mortality. 1,2 Previous studies elsewhere 3,4 and in Nigeria 5 have demonstrated left ventricular diastolic dysfunction (LVDD) in normotensive diabetics, supporting the existence of DMCMP.…”
mentioning
confidence: 85%